Work Experience from Paid Employment and the Path to Entrepreneurship: Business Takeover versus New Venture Start-Up - Guoqian Xi; Jörn Block; Frank Lasch; Frank Robert; Roy Thurik (Institute for the Study of Labor (IZA), 2016)
Our paper investigates how the type of work experience gained from prior paid employment influences the path to entrepreneurship. We distinguish between two distinct entrepreneurship entry modes: business takeover and new venture start-up. Using a large and rich French data set, we find that small firm experience increases the likelihood for business takeover, whereas management and same sector experience both increase the likelihood for new ventures. Our findings are relevant for policymakers aiming to improve the business transfer process.
Keywords: L26; 330; entrepreneurship entry mode; business takeover; new venture start-up; work experience